Analysis of the Concept of Zina in Tafsir Fii Dzilalil Qur’an by Sayyid Quthb and Its Relationship with Al-Maqashid Al-Khamsah - Didik Hariyanto; Mahfud; Muhammad Irwinsyah Putra; M. Aufa (Technium Education and Humanities, 2024)
This study aims to explain how tafsir fii Dzilali Al-Qur’an interprets the verses of zina in the Qur’an and how it relates to Hifzu An-Nasl, one of the parts of Al-Maqashid Al-Khamsah. One of the objectives of this study is to increase the collection of knowledge, provide references for research and scientific work, and provide knowledge about life before and after marriage. This research is a type of library research, and the model used is a qualitative research method that produces descriptive data. The study found that Sayyid Qutb, in his book Fii Dzilali of the Qur’an, argued that adultery is tantamount to murder, both physically and mentally to the child. The relationship between the interpretation of the verse zina and the meaning of murder is very closely related to Hifzu An-Nasl, one part of Al-Maqashid Al-Khamsah, because there is no adequate treatment for minors.